Perceived Organizational Support and Job-Hopping Motives Among Generation Z Employees in Banda Aceh - Sabrina, Atshalu Mauli; Andriyani, Juli (Fathana, 2026)
The phenomenon of job hopping has increasingly occurred among Generation Z employees, who tend to change jobs within a relatively short period. One of the factors assumed to influence this tendency is perceived organizational support, defined as employees’ perceptions of how much the organization values their contributions and cares about their well-being. This study aims to examine the relationship between perceived organizational support and job-hopping motives among Generation Z employees in Banda Aceh. This research employed a quantitative approach with a correlational method. The sample consisted of 121 Generation Z employees selected using purposive sampling technique. The instruments used were the Perceived Organizational Support scale (Rhoades & Eisenberger, 2002) and the Job-Hopping Motives scale (Lake et al., 2017). Data was analyzed using Spearman’s rho correlation. The results revealed a significant negative relationship between perceived organizational support and job-hopping motives (ρ = -0.662; p < 0.05). This indicates that higher perceived organizational support is associated with lower job-hopping motives among employees. These findings highlight the important role of organizations in enhancing support to reduce employees’ tendency to change jobs. Practically, organizations in Banda Aceh are encouraged to implement fair compensation systems, strengthen supervisor support through leadership training, and provide clear career development programs to retain Generation Z employees.